Bidirectional Synaptic Plasticity in the Cerebellum-like Mammalian Dorsal Cochlear Nucleus - Fujino, Kiyohiro; Oertel, Donata (Proceedings of the National Academy of Sciences - PNAS, 2003)
The dorsal cochlear nucleus integrates acoustic with multimodal sensory inputs from widespread areas of the brain. Multimodal inputs are brought to spiny dendrites of fusiform and cartwheel cells in the molecular layer by parallel fibers through synapses that are subject to long-term potentiation and long-term depression. Acoustic cues are brought to smooth dendrites of fusiform cells in the deep layer by auditory nerve fibers through synapses that do not show plasticity. Plasticity requires Ca2+-induced Ca2+ release; its sensitivity to antagonists of N-methyl-D-aspartate and metabotropic glutamate receptors differs in fusiform and cartwheel cells.